Does mandatory gender balance work? Changing organizational form to avoid board upheaval - Bøhren, Øyvind; Staubo, Siv (Journal of Corporate Finance, 2014)
Norway is the first, and so far the only, country to mandate a minimum fraction of female and male directors on corporate boards. We find that after a new gender balance law surprisingly stipulated that the firm must be liquidated unless at least 40% of its directors are of each gender, half the firms exit to an organizational form not exposed to the law. This response suggests that forced gender balance is costly. The costs are also firm-specific, because exit is more common when the firm is non-listed, successful, small, young, has powerful owners, no dominating family owner, and few female directors. These characteristics reflect high costs of involuntary board restructuring and low costs of abandoning the exposed organizational form. Correspondingly, certain unexposed firms hesitate to become exposed. Overall, we find that mandatory gender balance may produce firms with inefficient organizational forms or inefficient boards.